2022
DOI: 10.1108/mi-06-2022-0116
|View full text |Cite
|
Sign up to set email alerts
|

Two-step flash sintering of (Mg1/3Ta2/3)0.01Ti0.99O2 giant dielectric ceramics

Abstract: Purpose The purpose of this paper on the one hand is to reduce the sintering temperature, shorten the sintering time and improve the electrical properties of the sample through the two-step flash sintering method and on the other hand is to study the effect of electric field on the phase structure, microstructure and electrical properties of the flash sintering sample. Design/methodology/approach In this paper, (Mg1/3Ta2/3)0.01Ti0.99O2 giant dielectric ceramics were prepared by conventional sintering and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Many ceramic materials have been proved to be prepared by flash sintering, including ionic conductor (3YSZ 21 ), insulator (Al 2 O 3 22), semiconductor (ZnO, 23 TiO 2 24 ) and so on. Xu et al [25][26][27][28] found that flash sintering could obtain similar electrical properties to TS in TiO 2 -based CP ceramics. The dielectric properties of co-doped TiO 2 ceramics are summarized in Table III.…”
mentioning
confidence: 99%
“…Many ceramic materials have been proved to be prepared by flash sintering, including ionic conductor (3YSZ 21 ), insulator (Al 2 O 3 22), semiconductor (ZnO, 23 TiO 2 24 ) and so on. Xu et al [25][26][27][28] found that flash sintering could obtain similar electrical properties to TS in TiO 2 -based CP ceramics. The dielectric properties of co-doped TiO 2 ceramics are summarized in Table III.…”
mentioning
confidence: 99%